Evaluasi Kualitas Instrumen Tes Pilihan Ganda pada Mata Pelajaran IPA Kelas V Sekolah Dasar Berdasarkan Analisis Butir Soal: Penelitian - Kiki Fajariani; Erlia Hanum (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is a literature review that aims to evaluate the quality of multiple-choice test instruments in fifth-grade elementary school science subjects based on item analysis. Evaluation of test instruments is important to ensure that the questions used in the learning process can validly, reliably, and objectively measure students’ competencies. Through a review of various journals and relevant literature, this study analyzed several aspects of question quality such as validity and reliability, difficulty level, discriminating power, and distractor effectiveness. The results show that many multiple-choice questions used in science learning evaluations have not yet met good quality standards, thus affecting the accuracy of assessments of student learning outcomes. This study recommends the need for teacher training in question preparation and analysis as well as the use of item analysis technology. These findings are expected to serve as a basis for improving the quality of educational evaluation at the elementary school level.